Posterior approach to the Hip Joint - K Mohan Iyer (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2021)
The hip joint is one of the most surgically exposed joints in the body [1]. The posterior approach is known to have a slightly higher risk of dislocations [2], whilst the anterior [3] and lateral approaches [4] allow for preservation of the posterior soft tissue envelope. I had developed a modification of the Posterior Approach at a time when the regular Posterior Approach was plagued with the problem of dislocation. Hence this modification was devised after cadaveric tests confirming superiority by increasing its stability and thus prevent dislocation of the Hip joint. This is a posterior trochanter spliting approach to the Hip Joint by maintaining all the advantages of the Posterior Approach with excellent visualization of the Hip Joint. This was then used in patients with a fracture neck femur for insertion of an endoprosthesis.